Sor Juana Inés de la Cruz, Poemas. Ed. facsimilar. Instituto de Cooperación Iberoamericana, Madrid, 1993; 37 + 406 pp. - Tenorio, Martha Lilia (El Colegio de México, 1994)
Se reseñó el libro: Poemas. Ed. facsimilar.